Developing emerging leaders using professional learning conversations. Issue 5 (2nd September 2016) - Readman, Kylie; Rowe, Jennifer
ABSTRACT: Leadership in learning and teaching is a strategic priority for Australian universities, in that it is critical for improving the quality of higher education. Opportunities for academic staff to prepare for such leadership, especially during the early phases of their career, are not well embedded. This article reports on the implementation of a leadership development program for emerging leaders of learning and teaching in higher education that developed and utilised a professional learning conversation protocol. The results demonstrate that participating in the conversations had a range of positive outcomes for participants and the organisation in which the program was offered.